2011
DOI: 10.1128/jvi.02683-10
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Changes in the HIV Rev-Response Element Mediate Resistance to Compounds That Inhibit Rev Function

Abstract: Previously we described the identification of two compounds (3-amino-5-ethyl-4,6-dimethylthieno[2,3-b] pyridine-2-carboxamide [103833] and 4-amino-6-methoxy-2-(trifluoromethyl)-3-quinolinecarbonitrile[104366]) that interfered with HIV replication through the inhibition of Rev function. We now describe resistant viral variants that arose after drug selection, using virus derived from two different HIV proviral clones, NL4-3 and R7/3. With HIV NL4-3 , each compound selected a different single point mutation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Interestingly, the nucleotide changes that occurred between these RRE molecules were located outside the primary Rev binding domain, suggesting that other regions of the RRE contribute to the overall phenotype. These findings are consistent with previous experiments using laboratory-adapted viral clones, where it was demonstrated that one or two nucleotide changes in the RRE could dramatically alter both its structure and activity (23,24). It has now been established that regions of the RRE distant from the primary binding site play a role in multimerization and in modulating the affinity of the primary binding event (22,51).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, the nucleotide changes that occurred between these RRE molecules were located outside the primary Rev binding domain, suggesting that other regions of the RRE contribute to the overall phenotype. These findings are consistent with previous experiments using laboratory-adapted viral clones, where it was demonstrated that one or two nucleotide changes in the RRE could dramatically alter both its structure and activity (23,24). It has now been established that regions of the RRE distant from the primary binding site play a role in multimerization and in modulating the affinity of the primary binding event (22,51).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the structure and activity of the RRE are sensitive to minimal nucleotide changes (23,24). There- fore, it was of interest to analyze the individual activities of the different patient RREs to determine what role, if any, RRE sequence variability played in mediating Rev-RRE activity differences between patients and time points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5), that the thienopyridine compound 4a specifically targets the Rev-RRE reporter but not the HIV Tat-TAR reporter. The previous screen did not use the HIV LTR, and these investigators further uncovered a thienopyridine resistance mutation in the RRE, consistent with the Rev-RRE interaction as the target of thienopyridines (40). We have also generated this RRE-defective virus and shown that it is resistant to compound 4e (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Rev inducibility was lost when 10.5% of the codons were replaced with synonymous codons reflecting the codon usage of RRV gH. While it had been previously known that Rev induction depended on the Rev response element (the RRE) and the presence of a splice donor upstream of the coding sequence (11,18), the dependence on the nature of the skewed codon usage had not been previously known, although publications by Graf et al (14) and Shuck-Lee et al (19) are consistent with it. Similarly, our data show that ORF57 induction of RRV gH protein expression also depends on the nature of the skewed codon use.…”
Section: Discussionmentioning
confidence: 99%